3D‐printed photo‐spectroelectrochemical devices for in situ and in operando X‐ray absorption spectroscopy investigation. (2nd February 2016) - Achilli, Elisabetta; Minguzzi, Alessandro; Visibile, Alberto; Locatelli, Cristina; Vertova, Alberto; Naldoni, Alberto; Rondinini, Sandra; Auricchio, Ferdinando; Marconi, Stefania; Fracchia, Martina; Ghigna, Paolo
Abstract : A compact cell for photo‐spectroelectrochemical X‐ray absorption spectroscopy is presented. The cell has been fabricated by three‐dimensional printing and has been successfully used for in situ and in operando experiments. Abstract : Three‐dimensional printed multi‐purpose electrochemical devices for X‐ray absorption spectroscopy are presented in this paper. The aim of this work is to show how three‐dimensional printing can be a strategy for the creation of electrochemical cells for in situ and in operando experiments by means of synchrotron radiation. As a case study, the description of two cells which have been employed in experiments on photoanodes for photoelectrochemical water splitting are presented. The main advantages of these electrochemical devices are associated with their compactness and with the precision of the three‐dimensional printing systems which allows details to be obtained that would otherwise be difficult. Thanks to these systems it was possible to combine synchrotron‐based methods with complementary techniques in order to study the mechanism of the photoelectrocatalytic process.